Ex vivo and in vivo study of Kowa HA-2 applanation tonometer in the measurement of intraocular pressure in cats - Claudia Lizandra Ricci; Rogério Giuffrida; Glaucia Prada Kanashiro; Hilidia Stephania Rufino Belezzi; Carolina de Carvalho Bacarin; Michele Paulo Tenório; Bruna Toledo Duran Foglia; Silvia Franco Andrade (Semina: Ciências Agrárias, 2017)
The objective of this study was to evaluate the use of the Kowa HA-2 applanation tonometer in measuring intraocular pressure (IOP) in cats. Ten healthy eyes were used in an ex vivo study in which the calibration curve for manometry vs. tonometry was determined by artificially raising the IOP in 5 mmHg increments up to 60 mmHg (10-60 mmHg). Both eyes of 10 anesthetized cats were studiedin vivo to compare manometry vs. tonometry. In the ambulatory study, 78 healthy eyes, 7 eyes with glaucoma and 20 eyes with uveitis were evaluated by tonometry, which was performed with topical anesthesia and 1% fluorescein eye drops for the formation of fluorescein semicircles. The correlation coefficient (r²) between the manometer and the Kowa HA-2 tonometer was 0.993 and the linear regression equation was y = 0.0915x + 0.0878 in the ex-vivo study. In the in vivo study, the IOP values (mean±SD, in mmHg) in manometry were 15.6 ± 1.1(14.0 – 17.5) and in tonometry were 15.5 ± 1.2(13.5 – 17.2), with no significant difference (P > 0.05) between manometry and tonometry. In ambulatory study, using the Kowa HA-2 tonometer, the IOP values (mean±SD, in mmHg) were 15.0 ± 1.5 (11.8 – 18.3) for the healthy eyes, 38.4 ± 8.1(29.6 – 53.7) for glaucomatous eyes and 10.4 ± 2.0(5.3 – 12.2) for eyes with uveitis. There was a strong correlation and accuracy between the IOP values with the manometry and the Kowa HA-2 tonometer. In the ambulatorystudy the IOP values obtained with the tonometer were compatible for animals with healthy eyes and with clinical signs of glaucoma and uveitis. We conclude that the Kowa HA-2 tonometer can be used in the measurement of IOP in cats, since it is a practical and accurate method in this species.